What research on early childhood education/care outcomes can, and can't tell policymakers - Wylie, Cathy, 1951- (Wellington, N.Z. : New Zealand Council for Educational Research, 1994)
Introduction. Research on early childhood education/care-some necessary background. Outcomes of early childhood education/care. Funding and regulation factors bearing on the provision of early educare. Some conclusions for the present New Zealand situation.
Keywords: Education; Child development; Early childhood education; Early childhood education -- New Zealand; Education, Preschool; Day care centers; Education, Preschool -- New Zealand; Day care centers -- New Zealand